Diseño multimedia informativo sobre la alimentación saludable con productos andinos enfocada a estudiantes de la Universidad Técnica de Cotopaxi. - Alomoto Iza, Lucía Maribel (2019)
This research focuses on two factors: multimedia design and healthy food. Currently, the design has diversified in the use of mobile communications and technologies as digital multimedia resources in favor of entertainment; without relation to the consumption of Andean foods; therefore, the development of a multimedia proposal that reports timely on the intake of healthy food are limited. The compilation, analysis through bibliographic research, survey and interview allow to base on the design of a mobile prototype to inform about the benefits of a healthy diet based on Andean products; in the process of project development, Jesse James Garrett and Joan Costa’s methodology has been taken as a reference; which consists in the development of the imagetype as a starting point for structuring a proposal for a mobile informative guide. The use of graphic design tools and use of: photographic registration, color correction and mobile layout using Marvel, will be unified in order to design an information guide on the Android operating system, benefiting students of the Technical University of Cotopaxi, allowing to improve levels of consumption in favor of a healthy diet for the Utecina community, thereby, the presence in the mobile digital media allows to benefit and generate a higher level of knowledge about the extensive nutritional benefits of its consumption.